Influence of seed size on germination and vigor of seedlings of Camu-Camu - Mesquita Souza, Olisson (2017)
Camu-camu (Myrciaria dubia) is a fruit species native to the Amazon and its economic importance is proven because the fruit contains high content of ascorbic acid. The objective of this work was to evaluate the germination and vigor of seedlings obtained from seeds of different sizes of two camu-camu populations. The experimental design was completely randomized in a factorial scheme of 2 x 3 (two provenances river Anauá and river Urubu and three seed sizes, small, medium and large) with 5 replicates of 20 seeds per plot. The seeds of the origin of the Anauá river presented higher mass (1.46 g) compared to the origin of the Urubu river (0.78 g). The speed and emergence of seed germination presented better values for the population of the Anauá river, justifying the adoption of choice of origin for the formation of seedlings. For root length, dry shoot mass and dry mass of the root system, the seeds classified as medium and large originated from the Anauá river presented higher values. The size of the seeds is an important character to be used in the production of Myrciaria dubia seedlings. The seeds of the origin of the Anauá river are potentially more vigorous are indicate for the production of camu-camu (Myrciaria dubia) seedlings.